PERAN TEACHER STRUCTURE TERHADAP ENGAGEMENT MELALUI ACADEMIC BUOYANCY PADA SISWA MENENGAH ATAS - Cahyadi, Surya; Rohinsa, Meilani (Jurnal Studia Insania, 2019)
The current research aims to investigate whether students' ability to deal with academic problems daily or academic buoyancy can mediate the effect of teacher structure in predicting senior high school students? engagement.  The participant of the research consisted of 213 senior high school students (Female = 126; 59.2%; Male= 87; 40.8%). The age of participants? ranged between 15-18 years, with a mean of 15.41 (SD=0.53). The instrument in the current research included Teacher Structure Questionnaire, Academic Buoyancy Scale, and Engagement Questionnaire. Data analysis was conducted using multiple regression tests. Based on research findings, Academic buoyancy mediates the effect of teacher structure in predicting senior high school students? engagement.  The findings of the study were discussed under the light of relevant literature, and some suggestions were made for future research. This finding implies that teachers need to be aware that every student needs the ability to deal with everyday academic problems in school. The existence of teacher structure can fulfill this ability. This support will shape students' engagement with learning activities in the classroom.